Cryotechnology in lung and heart-lung transplantation - M. T. Bekov; I. V. Pashkov; N. P. Mozheiko; R. A. Latypov; D. O. Oleshkevich; K. S. Smirnov; E. F. Shigaev; Ya. S. Yakunin; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2023)
Bronchial complications, along with development and progression of chronic dysfunction on the background of chronic rejection, are factors that reduce the quality and life of lung and heart-lung recipients. They also increase the frequency of hospitalizations. Application of cryotechnology is based on the contact effect of extremely low temperatures on organs and tissues using a cryoprobe. This article demonstrates the experience of using cryotechnology in the diagnosis and treatment of complications in lung and heart-lung recipients.